Subwavelength-resolution label-free photoacoustic microscopy of optical absorption in vivo - Zhang, Chi (2010)
Optical absorption provides essential biological functional information but cannot be sensed by mainstream optical microscopy technologies directly, which detect fluorescence or scattering and may require undesirable labeling. Here we developed in vivo subwavelength-resolution photoacoustic microscopy (SW-PAM) that provides exquisitely high optical-absorption contrast due to nonfluorescent, or fluorescent, endogenous pigments. Having approached the ultimate diffraction-limited optical resolution, SW-PAM can resolve subcellular organelles. Vasculature and early-stage melanoma were imaged with 12:1 and 17:1 contrasts, respectively, without labeling. SW-PAM along with the scaled-up macroscopy, as the only technology that measures the same contrast origin over such a wide length scale, can potentially accelerate translation from microscopic research to clinical practice.